Euro-Med Abandoned Small(er) Towns. A landscape/ecological urbanism perspective for sustainable regeneration in Basilicata inlands - Alessandro Raffa (Anuari d’Arquitectura i Societat)
Inside a Mediterranean scenario of population asymmetries, this paper talks about and ongoing research that aims to highlight issues, identify a working method and tools able to support sustainable regenerative design strategies for abandoned historical small(er) towns and their landscapes, especially in inlands contexts. With these objectives, the research chooses Basilicata region, in the South of Italy, as emblematic for its structural marginality- morphological, infrastructural, social and economic -, bio-cultural diverse and diffused heritage and its seemingly unreversible depopulation process. Aging, low birth rates and high level of emigration has produced the abandonment of small(er) towns, of rural areas and, by the contrary, an increasing wilderness, changing the millennial settlement structure and impacting on socio-ecological resilience. Inside the theoretical framework of landscape/ecological urbanism and related design- oriented experimentations, the constellation of abandoned small(er) towns are interpreted as urban densities of a performative bio-cultural green infrastructure that could support, through design, the contemporary challenge of sustainable development, with a relational and glocal approach. Small(er) towns regeneration is view inside a more complex, interdisciplinary and holistic frame in which inter-scalarity, flux, dynamic and time variability are crucial. Performative bio-cultural green infrastructure, through the multiplication of public space, could support sustainable processes, in an ecological, economic and social sense. From an applicational point of view, the research intends to build a dynamic atlas for the regeneration of abandoned small(er) towns; the atlas is conceived both as a reading and a design tool able to support polyphonic and open process of sustainable regeneration.